2019
DOI: 10.1016/j.cocis.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Design and application of stimulus-responsive droplets and bubbles stabilized by phospholipid monolayers

Abstract: Biomimetic colloidal particles are promising agents for biosensing, but current technologies fall far short of Nature's capabilities for sensing, assessing, and responding to stimuli. Phospholipidcontaining cell membranes are capable of binding and responding to an enormous variety of biomolecules by virtue of membrane organization and the presence of receptor proteins. By tuning the composition and functionalization of simulated membranes, soft colloids such as droplets and bubbles can be designed to respond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Phase-shift NEs that can reversibly switch from liquid NE droplets to gaseous MBs (Scheme 1) when activated by heat, sound or light after having been positioned in target tissues currently draw considerable attention [102,130,[145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160]. P-SNEs benefit from the small initial size and relatively long intravascular circulation half-life (up to a few days) of NE droplets, allowing extravasation and retention in tumor tissue (the still debated EPR effect) [161,162], and, after vaporization, acquire the responsiveness of MBs to US (resonance, inertial cavitation and destruction) needed for on-demand, site-selected delivery of O 2 and other therapeutics (Table 6, Scheme 4).…”
Section: Perfluorocarbon Nanoemulsions That Phase-change Into Microbu...mentioning
confidence: 99%
“…Phase-shift NEs that can reversibly switch from liquid NE droplets to gaseous MBs (Scheme 1) when activated by heat, sound or light after having been positioned in target tissues currently draw considerable attention [102,130,[145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160]. P-SNEs benefit from the small initial size and relatively long intravascular circulation half-life (up to a few days) of NE droplets, allowing extravasation and retention in tumor tissue (the still debated EPR effect) [161,162], and, after vaporization, acquire the responsiveness of MBs to US (resonance, inertial cavitation and destruction) needed for on-demand, site-selected delivery of O 2 and other therapeutics (Table 6, Scheme 4).…”
Section: Perfluorocarbon Nanoemulsions That Phase-change Into Microbu...mentioning
confidence: 99%
“…On the basis of the experimental results mentioned above and related papers, , we discuss the characteristic responses of TS molecules to the DOPC molecular layer. Π for all of the samples utilized, that is, NE, NA, DE, DA, BA, and CA, was maintained at zero for A > 15 Å 2 molecule –1 (Figure S4 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…The phospholipid artificial membrane is used as a model cell membrane to investigate the mechanism of cell response because it is difficult to factor out intrinsic elements and their nature on the mechanism of chemical sensation in living organisms as a result of their complexity. Indeed, interactions between chemical species and functional groups in phospholipid artificial membranes have been reported to be associated with barrier homeostasis of cellular membranes in skin . It has also been reported that membrane fluidity of liposomes is affected by ODs. We recently evaluated the interaction between OD molecules and phospholipid molecular layers based on the spectroscopies and surface pressure ( Π )–area ( A ) isotherms .…”
Section: Introductionmentioning
confidence: 99%
“…Like many other NPs applied intravenously, PVA-based MBs are also prone to become uptaken by the reticuloendothelial system; however, they stay in the blood circulation long enough to act as an efficient contrast agent [ 219 ]. Some novel nanosystems that have been developed are composed of liquid PFCs, perfluorohexane (PFH), PFP, phosphatidylethanolamine, and halocarbons as probes for US molecular imaging applications and as carriers for drug/gene delivery [ 129 , 171 , 220 ].…”
Section: Reviewmentioning
confidence: 99%